2018
DOI: 10.1186/s12984-018-0406-7
|View full text |Cite
|
Sign up to set email alerts
|

Economic value of orthotic and prosthetic services among medicare beneficiaries: a claims-based retrospective cohort study, 2011–2014

Abstract: BackgroundThere are few studies of the economic value of orthotic and prosthetic services. A prior cohort study of orthotic and prosthetic Medicare beneficiaries based on Medicare Parts A and B claims from 2007 to 2010 concluded that patients who received timely orthotic or prosthetic care had comparable or lower total health care costs than a comparison group of untreated patients. This follow-up study reports on a parallel analysis based on Medicare claims from 2011 to 2014 and includes Part D in addition to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 19 publications
0
28
0
Order By: Relevance
“…Finally, KID only provides a total charge for the admission, a markup of costs determined by each hospital. 40 We used cost-to-charge ratios that represented markup practices aggregated across the entire hospital; this may not accurately reflect the costs of individual departments. However, past studies have suggested that the difference is generally less than 10% 41 and that similar admissions, such as those within a DRG group, are likely to use similar resources across organizations, further decreasing between-hospital variation.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, KID only provides a total charge for the admission, a markup of costs determined by each hospital. 40 We used cost-to-charge ratios that represented markup practices aggregated across the entire hospital; this may not accurately reflect the costs of individual departments. However, past studies have suggested that the difference is generally less than 10% 41 and that similar admissions, such as those within a DRG group, are likely to use similar resources across organizations, further decreasing between-hospital variation.…”
Section: Discussionmentioning
confidence: 99%
“…We will argue that prosthetic care is so important for the overall health of users that it is economically beneficial for health insurances to deliver the best possible care. This has already been pointed out in some studies [8,9], but is still not widely acknowledged by insurances, in Germany also due to the short-term budget allocation scheme in the health care system [10] (p. 61). We posit that there are ways to efficiently improve prosthetic care, minimising the burden on the health care budget, in particular social aspects of acceptance are taken more systematically into account.…”
Section: Introductionmentioning
confidence: 92%
“…By doing so, probably not only quality of life may improve but also resources may be allocated more efficiently by reducing long-term negative side effects of failed prosthetic care such as a lack of acceptance of and adaptation problems with prostheses as well as by reducing costs in its research and development phase. It has already been shown, for example, that prosthetic care for high-cost knee prostheses is beneficial for the insurance budget in the long term, if compared to the use of such prostheses without care [8,9]. Biddiss et al point out that there are possibilities to reduce costs of prosthetic limbs by technical means like computer-aided design and manufacturing, and due to new market opportunities [1].…”
Section: Improvements Of Prosthetic Care From the Perspective Of Socimentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, O&P services can reduce health care spending via better patient outcomes, which in turn reduce other types of health care utilization [10,11]. Long-term savings are thought to result when patients receive appropriate orthotic and prosthetic care.…”
Section: Introductionmentioning
confidence: 99%